KAJIAN OPTIMALISASI RUTE PENGANGKUTAN SAMPAH DI KOTA PONTIANAK - Muhardi, Zeldi (Jurnal Teknik Sipil, 2015)
Pontianak city is the largest city and also the capital city of West Kalimantan. Along with the rapid development in Pontianak City, the city is now facing waste management issue due to waste disposal and transport which require serious attention. The fact showed that waste is not totally collected and transported. Moreover, there are still many illegal waste disposal sites which have not been handled by Cleaning and Landscaping Agency.                       Waste management issue seen from the disposal of waste to river, canal or empty land, causing only a small number of transported waste to the landfill. In addition, lack of human resources, financing as well as facilities in waste management are not in accordance with the waste produced by Pontianak people"™s activities. These actually underlie the importance of analyzing the relationship of waste management aspects in order to improve the service of waste management performance in Pontianak City.                       Analyzing the relationship of management aspects toward the management performance, thenear regression statistic analysis was employed by calculating the number of routes of each vehicle. Meanwhile, the assessment toward the management performance of waste done by using SWOT Analysis. According to the research result, the level of waste service currently is 79,24%, in which the route for transporting by the dump truck was 2 routes, while arm roll was 3 routes. Alternative solutions improving the performance of Cleaning and Landscaping Agency of Pontianak City is indispensable to address the inefficiency of waste management in Pontianak City  Keywords: waste, optimal, routes.